2020
DOI: 10.18502/ijph.v49is1.3680
|View full text |Cite
|
Sign up to set email alerts
|

Can Increasing the Number of Close Contact Lead to More Mortality in COVID-19 Infected Patients?

Abstract: This article is a Letter to the Editor and does not include an Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…We have previously reported that reducing close contact is the only effective way to fight the COVID-19 virus ( Hormati, Ghadir, Foroghi Ghomi, et al, 2020 ). As a result, we have attempted to conduct most of our clinical visits virtually and reserve high-risk diagnostic methods only for emergencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that reducing close contact is the only effective way to fight the COVID-19 virus ( Hormati, Ghadir, Foroghi Ghomi, et al, 2020 ). As a result, we have attempted to conduct most of our clinical visits virtually and reserve high-risk diagnostic methods only for emergencies.…”
Section: Resultsmentioning
confidence: 99%
“…From February 21 to June 20, 2020, more than 89,000 cases have been diagnosed with COVID-19 in the authors' country of Iran, with 6,150 deaths reported ( Jahangiri, Jahangiri, & Najafgholipour, 2020 ; Nikpouraghdam et al, 2020 ; Shojaee et al, 2020 ). Staying at home or quarantining in an isolated center and minimizing going out are effective ways to battle the spread of COVID-19 ( Aminnejad & Hormati, 2020 ; Hormati, Ghadir, Foroghi Ghomi, et al, 2020 ; Hormati, Ghadir, Zamani, et al, 2020 ; Hormati, Niya, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the role of the oral cavity as a portal for the entry of the virus into the body and as a viral reservoir can be controlled through the use of antiseptics at two levels. First, by reducing pathogenicity (the decrease in SARS-CoV-2 viral load has been associated with a reduction in the severity of COVID-19) [ 24 , 25 ] and second, by reducing transmission of the virus (by lowering the viral load, the amount of virus shed by the patient may be temporarily reduced, thus reducing the risk of transmission). But the likely impact of daily use of these antiseptics for limited periods of time on viral transmission has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, it is of utmost importance that asymptomatic patients be identified and warnings are given, concerning these carriers to control the epidemic. 12,13 So far, various tests have been developed to confirm the diagnosis of COVID-19. However, some of these methods only have diagnostic potentials for patients with symptoms during the 14 days after contact.…”
Section: Discussionmentioning
confidence: 99%